2020
DOI: 10.3390/biom10081087
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Immunosuppressive Cells as a Target for Immunotherapies in Melanoma and Non-Melanoma Skin Cancers

Abstract: Tumor-associated macrophages (TAMs) have been detected in most skin cancers. TAMs produce various chemokines and angiogenic factors that promote tumor development, along with other immunosuppressive cells such as myeloid-derived suppressor cells (MDSCs), regulatory T cells (Tregs) and tumor-associated neutrophils. TAMs generated from monocytes develop into functional, fully activated macrophages, and TAMs obtain various immunosuppressive functions to maintain the tumor microenvironment. Since TAMs express PD1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 99 publications
0
47
0
Order By: Relevance
“…In another report, Irimada et al found a correlation between serum CXCL5 levels and onset of rhabdomyolysis caused by D + T therapy [43]. Since all of these soluble factors described above are well-known TAM-related factors [46], BRAF/MEK inhibitors might activate TAMs in advanced melanoma patients directly or indirectly, leading to production of these soluble factors and development of characteristic AEs.…”
Section: Adverse Events With Braf/mek Inhibitorsmentioning
confidence: 96%
“…In another report, Irimada et al found a correlation between serum CXCL5 levels and onset of rhabdomyolysis caused by D + T therapy [43]. Since all of these soluble factors described above are well-known TAM-related factors [46], BRAF/MEK inhibitors might activate TAMs in advanced melanoma patients directly or indirectly, leading to production of these soluble factors and development of characteristic AEs.…”
Section: Adverse Events With Braf/mek Inhibitorsmentioning
confidence: 96%
“…Recent report suggested PD-1-PD-L1 therapies may also function through a direct effect on TAMs, and when PD-L1/PD-1 signaling is blocked by antibodies, CD163+ TAMs activated and polarized into M1-like TAMs 68 . Since the profiles of chemokines are different between M1 and M2 polarized macrophages, M1-polarized macrophages not only induce cytotoxic reaction against lymphoma cells, but also work together with other immunosuppressive cells 69 .…”
Section: T-cell Exhaustion Via Immune Checkpointsmentioning
confidence: 99%
“…On the other hand, TAMs are involved in cancer progression through the release of specific protumoral cytokines such as interleukin IL-6, IL-8 and IL-10 [ 37 , 38 , 39 , 40 ]. TAMs are also able to express immune checkpoint modulators such as PD-L1 and various chemokines (C-C motif chemokine ligand 17 (CCL17), CCL22, C-X-C motif chemokine ligand 10 (CXCL10)) which attract effector/activated T regs that exert an immunosuppressive action and promote tumor growth ( Figure 1 C) [ 36 , 37 , 38 , 41 , 42 , 43 ].…”
Section: Immunopathology Of Vcmentioning
confidence: 99%